A comparative study of neuropharmacological properties of Tabernaemontana divaricata (Apocynaceae) leaves extracts in a Swiss albino mouse model - Reddy, Konatham Teja Kumar; Gupta, Jeetendra Kumar; Prabitha, P.; Mubeen, M.; Syed, Sabeena Hussain; Dhunmati, K.; Bodapati, Anoop; Taru, Poonam Popatrao; Krosuri, Pavankumar; Prasad, P. Dharani (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Interest in natural products and nutraceuticals for the treatment of mental diseases such as anxiety, stress, sadness, and psychosis has increased due to their high safety index and cost. The primary objective of this work was to analyze the neuropharmacological attributes of leaf extracts of Tabernaemontana divaricata using models from Swiss albino mice. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Methanol, acetone, and ethyl acetate extracts were prepared from authenticated T. divaricata leaves. Experiments were conducted on 170 mice to evaluate the effects of thiopental sodium on sleeping time, hole cross, hole board, and open field behaviors. The duration of sleep caused by thiopental sodium was assessed at several doses, including 50 mg/kg, 100 mg/kg, and 200 mg/kg of body weight. Additionally, doses of 100 mg/kg and 200 mg/kg of body weight were used in the remaining tests. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. All extracts significantly increased thiopental-induced sleeping time in a dose-dependent manner, with maximum effects observed at 200 mg/kg (methanol: 684.77%, acetone: 655.63%, ethyl acetate: 666.89%). Locomotor and exploratory behaviors were reduced in all behavioral models, including a significant decrease in head dips and square crossings (p<0.01), supporting central nervous system depressant activity. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The study reveals that extracts of T. divaricata exhibit depressive and hypnotic effects on the central nervous sys tem, indicating the need for further research.